Sperm ultrastructure and a new type of spermiogenesis in two species of Pimelodidae, with a comparative review of sperm ultrastructure in Siluriformes (Teleostei : Ostariophysi) - Quagio-Grassiotto, Irani [UNESP]; Oliveira, Claudio [UNESP] (Elsevier Gmbh, Urban & Fischer Verlag, 2008)
During spermiogenesis, the spermatids of the pimelodid species Pimelodus maculatus and Pseudoplatystoma fasciatum show a central flagellum development, no rotation of the nucleus, and no nuclear fossa formation, in contrast to all previously described spermatids of Teleostei. These characteristics are interpreted as belonging to a new type of spermiogenesis, named here type III, which is peculiar to the family Pimelodidae. In P. maculatus and P. fasciatum, spermatozoa possess a spherical head and no acrosome; their nucleus contains highly condensed, homogeneous chromatin with small electron-lucent areas; and a nuclear fossa is not present. The centriolar complex lies close to the nucleus. The midpiece is small, has no true cytoplasmic channel, and contains many elongate and interconnected vesicles. Several spherical to oblong mitochondria are located around the centriolar complex. The flagellum displays the classical axoneme (9 + 2) and no lateral fins. Only minor differences were observed among the pimelodid species and genera. Otherwise, spermiogenesis and spermatozoa in the two species of Pimelodidae studied exhibit many characteristics that are not found in other siluriform families, mainly the type III spermiogenesis. (C) 2007 Elsevier GmbH. All rights reserved.
Keywords: catfish; spermatid; sperm; morphology; evolution; Teleostei